Carbapenem Therapeutic Drug Monitoring in Critically Ill Adult Patients and Clinical Outcomes: A Systematic Review with Meta-Analysis - Sharon Lechtig-Wasserman; Hans Liebisch-Rey; Nicolas Diaz-Pinilla; Jhosep Blanco; Yuli-Viviana F; Rosa-Helena Bustos (MDPI AG, 2021)
Drug monitoring is one strategy of antibiotic stewardship to face antimicrobial resistance. This strategy could have a determinant role in critically ill patients treated with carbapenems to overcome pharmacokinetic variability, reduce the risk of subtherapeutic dosage or toxicity, and reduce the risks inherent to treatment. However, the effectiveness of therapeutic drug monitoring (TDM) is unknown. This paper aims to identify TDM effectiveness in critically ill patients treated with carbapenems. English and ClinicalTrials.gov databases were searched to identify relevant studies evaluating carbapenem TDM. Randomized controlled trials (RCTs) and comparative cohort studies were selected for inclusion if they compared carbapenem TDM to standard care in adult critically ill or sepsis/septic shock patients. The primary outcome was mortality. Secondary outcomes included morbidity, clinical cure, microbiological eradication, antimicrobial resistance, drug-related side effects, and achievement of target plasma concentrations. Overall, performing carbapenem TDM was not associated with a decrease in mortality. However, it could be evidence for a relationship with clinical cure as well as target attainment. Some studies found favorable outcomes related to clinical and microbiological responses, such as lower procalcitonin levels at the end of the monitored therapy compared to standard care. For the primary and secondary outcomes analyzed, strong evidence was not identified, which could be due to the size, risk of bias, and design of selected studies.